1989
DOI: 10.1098/rspa.1989.0065
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial control of nucleation of calcium carbonate under organized stearic acid monolayers

Abstract: The nucleation and crystal growth of calcium carbonate from supersaturated bicarbonate solutions in the presence of stearic acid monolayers has been studied by electron microscopy and electron and X-ray diffraction. Whereas rhombohedral crystals of calcite are randomly deposited in the absence of the monolayer, regiospecific crystallization of vaterite florets occurs at the organic surface. The florets develop initially as single crystalline biconvex discs oriented with respect to the negatively charged headgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 23 publications
2
12
1
Order By: Relevance
“…As a result, a hydrophobic alkyl chains is chemisorbed to the mineral surface, thus affecting the surface forces between the filler and the polymer matrix. On the other hand, the knowledge on the minimum quantity of fatty acid molecules that could produce the hydrophobic precipitate suitable for use as filler in polymer materials is of importance, because the precipitation could affect crystal nucleation and/or crystal growth of CaCO 3 [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a hydrophobic alkyl chains is chemisorbed to the mineral surface, thus affecting the surface forces between the filler and the polymer matrix. On the other hand, the knowledge on the minimum quantity of fatty acid molecules that could produce the hydrophobic precipitate suitable for use as filler in polymer materials is of importance, because the precipitation could affect crystal nucleation and/or crystal growth of CaCO 3 [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Langmuir monolayer is an excellent candidate for this purpose: they are already in contact with water, they are ordered, and their structures are well-known and can be varied by changing pressure, temperature and other experimental parameters. Recently, the nucleation of inorganic crystals under Langmuir monolayer has been extensively studied [13][14][15][16][17][18]. Mann and coworkers have performed extensive studies of the nucleation of calcium carbonate [13,14], barium sulfate [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the nucleation of inorganic crystals under Langmuir monolayer has been extensively studied [13][14][15][16][17][18]. Mann and coworkers have performed extensive studies of the nucleation of calcium carbonate [13,14], barium sulfate [15]. They found that preferentially nucleated crystals would be prepared under organic Langmuir monolayer with specific polymorphs and specific lattice orientations.…”
Section: Introductionmentioning
confidence: 99%
“…A new field, usually named biomineralization, has received considerable attention and has been developed very rapidly in recent years. A development in this area involves the use of Langmuir monolayers of surfactant molecules as molecular templates for the oriented nucleation of organic and inorganic crystals. Because of ion binding, lattice matching, and structural and stereochemical complementarity between the monolayer and the crystal, very high selectivity in the nucleation and growth of crystal can be observed. The ability to control the crystallization of inorganic solids is critical to improve technological use of materials currently and in the future …”
Section: Introductionmentioning
confidence: 99%